Microdialysis as a Tool for Drug Quantification in the Bronchioles of Anaesthetized Pigs. (26th October 2013) - Rottbøll, Lisa A. H.; Friis, Christian
Abstract Target site drug determinations are crucial for optimizing treatment of infectious diseases. There is limited knowledge of antibiotic drug penetration into the pulmonary epithelial lining fluid (PELF) and a lack of easily performed methods for continuous drug sampling hereof. The aim of this study was to develop a readily accessible microdialysis (MD) method for antibiotic drug quantification in PELF of pigs. The fluoroquinolone danofloxacin was administered to anaesthetized pigs allocated to three groups: intravenous injection, intravenous infusion and intramuscular injection. MD probes were guided through a tracheostomy into the distal bronchioles using an insertion tube. Intravenously administered inulin served as a marker of extracellular fluid contamination of PELF. Concentrations of free drug in MD fractions were compared to total and non‐protein‐bound drug concentrations in plasma. Rising and declining danofloxacin plasma concentrations were rapidly reflected in PELF, suggesting an efficient drug transport across the blood bronchial barrier. The AUC FREE DRUG PELF/AUC FREE DRUG PLASMA ratio was 1.8 (S.D. 0.4, 95% CL 1.4–2.3). Although the probes were placed without fiberscopic or other special equipment, the danofloxacin concentrations in PELF were consistent within the different administration groups. The described MD method for drug quantification in PELF is easily accessible and provides repeatable results. However, trace amount of inulin was detected in the MD fractions, suggesting a local tissue reaction induced by the MD membrane. The significance of this finding needs to be clarified in future studies.